Physical properties of beech wood thermally modified in hot oil and in hot air at various temperatures - Cihad Bal, Bekir (Maderas. Ciencia y Tecnología, 2025)
In this study, beech wood was treated in hot oil and in hot air to determine the differences in the effects of the two processes on the physical properties of the wood. Heat treatment was conducted at temperatures of 160, 190, and 220 °C for 2 h at atmospheric pressure. After the heat treatment, various properties of the wood, including mass increase in hot oil treatment (wt% gain), mass loss in hot air treatment (wt% loss), oven-dried density, swelling, equilibrium moisture content, fiber saturation point, and moisture content were determined. Regression analyses were conducted to assess the differences in mass change and volumetric swelling, and the findings were analyzed statistically. The results showed that heat treatment in hot oil influenced the physical properties of beech wood more than treatment in hot air. However, the extensive uptake of oil by the wood samples, resulting in mass increases, was a negative issue associated with the hot oil treatment.